The Radicalization of Diasporas and Terrorism A Joint Conference by the RAND Corporation and the Center for Security Studies, ETH Zurich - Hoffman, Bruce (RAND Corporation, 2007)
Certain Diaspora communities, frustrated by a perceived war against the Muslim world, have turned against their adopted homelands, targeting the government and its people by supporting terrorist attacks against Western countries through recruitment, fundraising, and training. The problem is exacerbated by the open borders of globalization. Emerging threats must be identified without alienating Diaspora communities and thereby playing into terrorist hands.